ChemInform Abstract: Structural Transformations and Disordering in Zirconolite (CaZrTi2O7) at High Pressure. Issue 16 (28th March 2013) - Salamat, Ashkan; McMillan, Paul F.; Firth, Steven; Woodhead, Katherine; Hector, Andrew L.; Garbarino, Gaston; Stennett, Martin C.; Hyatt, Neil C.
Abstract The mineral zirconolite (CaZrTi2O7) shows a series of high pressure phase transformations.